Pengaruh Pemberian Kunyit Asam dengan Jus Nanas terhadap Penurunan Nyeri Disminore Primer pada Remaja Putri di TPMB 'M' Belitung Timur - Mawa Datturohma; Fanni Hanifa; Hidayani Hidayani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Menstrual pain or dysmenorrhea is a common complaint experienced by adolescent girls throughout the world has shown that the incidence of dysmenorrhea is quite high, namely 43-93% of women experience dysmenorrhea and 5-10% of them experience very severe dysmenorrhea and leave their activities 1-3 days a month, where 8% of them have to leave school or work during menstruation The purpose of this study is to examine the effect of giving turmeric and tamarind with pineapple juice on reducing primary dysmenorrhea pain in TPMB "M".This study uses a qualitative research strategy, with a case study, which is a series of scientific activities carried out intensively, in detail and in depth about a program, event, and activity, both at the individual level, a group of people, institutions, or organizations to obtain in-depth knowledge about the event, this case study was conducted directly to adolescents who were menstruating and experiencing primary dysmenorrhea. The results of the study were conducted in Case 1, an adolescent who was experiencing Primary Dysmenorrhea pain with a pain scale of 9 after being given Turmeric Acid, the NRS value at Visit 1 was 7, Visit 2 was 5, Visit 3 was 3. While in Case 2 after being given Pineapple juice, the NRS value at Visit 1 was 7, Visit 2 was 4, Visit 3 was 2. both were the same in reducing pain, but consuming Turmeric Acid was more effective in reducing pain by 1 on the 2nd visit and the difference in pain reduction was 1 on the 3rd visit. It is hoped that this study can be used to add new knowledge about the treatment of dysmenorrhea pain in adolescents in a non-pharmacological way, namely by using turmeric acid and pineapple juice. as an alternative.